2021
DOI: 10.1093/toxres/tfab083
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effects of hesperidin andN-acetylcysteine against formaldehyde-induced-hemato- and genotoxicity

Abstract: This study investigated the hemato- and genotoxic effects of formaldehyde (FA) and the possible mitigating role of hesperidin (HP) and N-acetylcysteine (NAC), each alone and in combination. Sixty-four adult male albino rats were divided into eight equal groups; the study was conducted for 8 weeks; Group I (negative control: received no medication), Group II (positive control: received distilled water), Group III (received HP 50 mg/kg/day), Group IV (received NAC 50 mg/kg/day), Group V (received FA 10 mg/kg/day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
0
0
0
Order By: Relevance
“…Similarly, we found that the ethanolic extract of H. drummondii counteracted the deleterious effect of FA, and the group treated only with this extract showed no adverse effects on the evaluated parameters. Likewise, we can attribute the induced damage to the oxidative stress pathway activated by FA [14] and highlight the fact that the H. drummondii extract components were able to protect the testicular epithelium since not damage was observed.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Similarly, we found that the ethanolic extract of H. drummondii counteracted the deleterious effect of FA, and the group treated only with this extract showed no adverse effects on the evaluated parameters. Likewise, we can attribute the induced damage to the oxidative stress pathway activated by FA [14] and highlight the fact that the H. drummondii extract components were able to protect the testicular epithelium since not damage was observed.…”
Section: Discussionmentioning
confidence: 64%
“…Likewise, studies in rats exposed intraperitoneally to FA found changes in cells of the germinal epithelium (GE), decreased motility and sperm concentration, and increased sperm DNA fragmentation [9][10][11]. Furthermore, it has been reported that FA can increase reactive oxygen species production; molecules that play a central role in oxidative stress induction and cell damage [12][13][14]. Oxidative stress plays a critical role in testicular damage, however, one alternative for its prevention is the increase of dietary intake of antioxidants through the consumption of herbal infusions, mainly those obtained from the infusion of herbal species belonging to the Lamiaceae family.…”
Section: Introductionmentioning
confidence: 99%
“…The rise was statistically significant (p <0.05). Research by Mohammed et al, (2021) also showed that there was an increase in malondialdehyde levels in rat serum due to formaldehyde induction.…”
Section: Discussionmentioning
confidence: 94%